A tabayeva S.D., Nurmahanova A.S., Asrandina S.S., Alybayeva R.A., Kenzhebayeva S.S. Plants under the combined effect of salinity and heavy metals: 1Al-Farabi Kazakh national university, Research Institute of Ecology Problems, Almaty, Kazakhstan *Е-mail: sauleat@yandex.ru (Eurasian Journal of Ecology, 2017)
Large areasof soil and water, particularly in the vicinity of largecities and large industrial complexesare contaminated with heavy metals. Another environmental problem is a salinity. The main threat towater resources in many countries is irrigated agriculture. Saline ground water accelerate salinizationof soils. Salinization of ground water as desertification factor has two major aspects: the growth of saltmarsh deserts in drainage basins and salinization of irrigated lands. The proportion of saline soils is about20% of the entire area of irrigated arable land. The result is the combined effect of salinity and heavymetals on the ecosystems. In these areas, agriculture is developing, and there are located wheat, barleyand other crops. Heavy metals and salinity cause changes in the physiological, biochemical processesdue to accumulation of toxic ions in plant parts. In the review are presented data on the effect of heavymetals and salinity on plant growth and biomass accumulation, effect of different concentrations ofheavy metals like cadmium, nickel, sinc, copper and sodium chloride on plants growth. The joint effectof salinity and heavy metals is expressed in a change of anatomical parameters of leaves as a reductionin the thickness of the upper and lower epidermis, reducing the diameter of the conductive beams as anadaptive response to the flow of ions and salts of heavy metals. Change the anatomical parameters ofplants roots under the combined effect of salinity and heavy metals is expressed in increasing exodermthickness, providing a peripheral barrier to the penetration of toxic ions in the apoplast. An anatomicalindicator that affect the level of the whole organism - the diameter of the vascular bundles, the ratioexoderm thickness to the thickness of the endoderm, the diameter of the central cylinder can be usedas a test for the resistance of plants to heavy metals and salinity. Under the combined effect of salinityand heavy metal the physiological and biochemical parameters such as growth and accumulation ofbiomass, relative water content, content of photosynthetic pigments are reduced and the level of lipidperoxidation as an oxidative stress index is increased. In response to salinity and heavy metals the activity of antioxidant enzymes, polyamines, stressful amino acids as integral indicators of plant resistanceare increased. The combined effect of heavy metals and salinity aggravates the separate effect of bothstressors by increasing osmotic stress, as a result of the high level of dehydration (RWC) and the toxiceffect of salinity (NaCl) and heavy metals ions.